Child labor in the Philippines a review of selected studies and policy papers - Del Rosario, Rosario; Bonga, Melinda A. (Office of the Vice Chancellor for Research and Development, University of the Philippines, 2000)
Child labor robs children of their childhood. It jeopardizes their health and education. It grabs their leisure moments for exploration, discovery and experimentation, so necessary for a promising life. It ensures the perpetuation of poor communities in society. This book contains the stories of child workers and their unfortunate situations. It also assesses the terrain of child labor in the Philippines, and the research and advocacy experiences of those who have spent time to study such a complex, seemingly invisible reality in the 10 years between 1986-1995.